Addressing the third delay: implementing a novel obstetric triage system in Ghana. Issue 2 (17th April 2018) - Goodman, David M; Srofenyoh, Emmanuel K; Ramaswamy, Rohit; Bryce, Fiona; Floyd, Liz; Olufolabi, Adeyemi; Tetteh, Cecilia; Owen, Medge D
Abstract : Institutional delivery has been proposed as a method for reducing maternal morbidity and mortality, but little is known about how referral hospitals in low-resource settings can best manage the expected influx of patients. In this study, we assess the impact of an obstetric triage improvement programme on reducing hospital-based delay in a referral hospital in Accra, Ghana. An Active Implementation Framework is used to describe a 5-year intervention to introduce and monitor obstetric triage capabilities. Baseline data, collected from September to November 2012, revealed significant delays in patient assessment on arrival. A triage training course and monitoring of quality improvement tools occurred in 2013 and 2014. Implementation barriers led to the construction of a free-standing obstetric triage pavilion, opened January 2015, with dedicated midwives. Data were collected at three time intervals following the triage pavilion opening and compared with baseline including: referral indications, patient and labour characteristics, waiting time from arrival to assessment and the documentation of a care plan. An obstetric triage improvement programme reduced the median (IQR) patient waiting time from facility arrival to first assessment by a midwife from 40 min (15–100) to 5 min (2–6) (p<0.001) over the 5-year intervention. The triage pavilion enhanced performance resulting in the elimination of previous delays associated with the time of admission and disease acuity. Care plan documentation increased from 51% to 96%. Obstetric triage, when properly implemented, reduced delay in a busy, low-resource hospital. The implementation process was sustained under local leadership during transition to a new hospital.